The Influence of Animated Video Media Regarding Endemic Polio Prevention Efforts on The Level Of Knowledge in Medical Faculty Students at Malikussaleh University - Zara, Noviana; Maulina, Nora; Lubis, Dzakwan Hakim (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Pre-clinical students need good knowledge about polio to make Indonesia a polio-free country again. Previous studies show that the level of knowledge about polio among the majority of pre-clinical  students is still not in the good category. Interesting health education can be done using animated videos. Animated videos have the advantage of displaying interactive images and animations. The aim of this research is to determine the influence of animated video media regarding efforts to prevent endemic polio on the level of knowledge of FOM Unimal Lhokseumawe City students. The research used a quasi-experimental research method with a one group pretest-posttest design involving 206 respondents. Data collection was carried out using a questionnaire sheet. The results of the research were that there were more female respondents than male respondents with the majority being in the late teenage age group (18-21 years). The results of this research were that there was an increase in knowledge of 51.0% in the good category after the intervention was carried out. The use of animated videos has an influence on knowledge based on the results of the Wilcoxon test with p of 0.000. This study concludes that there is an influence of animated video media on knowledge of endemic polio prevention efforts among FOM Unimal Lhokseumawe City students.